2007
DOI: 10.1111/j.1542-4758.2007.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sevelamer on aortic pulse wave velocity in patients on hemodialysis: A prospective observational study

Abstract: Aortic stiffening and aortic calcification are risk factors for cardiovascular events in hemodialysis (HD) patients, and these 2 risk factors are interrelated. Sevelamer decreases aortic calcification but its effect on aortic stiffness has not been investigated previously. Thirteen HD patients commencing sevelamer treatment and 13 matched controls were followed for 11 months. Aortic pulse wave velocity (PWV), augmentation index (AIx), and levels of inhibitors of vascular calcification (fetuin-A, matrix-GLA-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 23 publications
(24 reference statements)
0
17
0
1
Order By: Relevance
“…High serum OPG levels are associated with the progression of carotid atherosclerosis and coronary calcification in the general population, and a similar trend has been noted in HD patients [22,23,24]. Kim et al [25 ]reported a significant link between serum OPG levels and vascular stiffness.…”
Section: Discussionmentioning
confidence: 89%
“…High serum OPG levels are associated with the progression of carotid atherosclerosis and coronary calcification in the general population, and a similar trend has been noted in HD patients [22,23,24]. Kim et al [25 ]reported a significant link between serum OPG levels and vascular stiffness.…”
Section: Discussionmentioning
confidence: 89%
“…The PulsePen device has been previously described in details. [27][28] Herein, when the difference between heart rate recorded during the carotid measurement and that recorded during the femoral measurement was equal or greater than 10%, the PWV measurement was repeated (the difference in heart rate is indicated in the PulsePen software). According to this procedure, measurement of PWV had to be repeated in seven subjects.…”
Section: Reference Methodsmentioning
confidence: 99%
“…Two small observational studies showed that the use of Sevelamer, a noncalcium-containing phosphate binder, may significantly attenuate PWV deterioration in CKD patients receiving chronic dialysis [22, 23]. In another small series of 132 patients new to dialysis, the use of Sevelamer was associated with a significant reduction in the risk of PWV increase during the first 12 months of dialysis (odds ratio: 0.86; 95%CI 0.83–0.91, P = .05) [12].…”
Section: Therapeutic Approaches To Arterial Stiffness and Impact Omentioning
confidence: 99%